Different forms and sources of iron in relation to colorectal cancer risk: a case–control study in China. Issue 7 (23rd January 2019) - Luo, Hong; Zhang, Nai-Qi; Huang, Jing; Zhang, Xin; Feng, Xiao-Li; Pan, Zhi-Zhong; Chen, Yu-Ming; Fang, Yu-Jing; Zhang, Cai-Xia
Abstract: Few studies have examined the association of various types of Fe with colorectal cancer risk. The aim of this study was to investigate different forms and sources of Fe in relation to colorectal cancer risk in a Chinese population. A total of 2138 patients with colorectal cancer and 2144 sex- and age-matched (5-year interval) controls were recruited from July 2010 to November 2017. Dietary information was assessed by face-to-face interviews using a validated FFQ. Multivariable logistic regression was used to estimate the OR and 95 % CI on models. Intake of Fe from plants and Fe from white meat were inversely associated with the risk of colorectal cancer, while haem Fe and Fe from red meat were positively associated with colorectal cancer risk. The multivariable OR for the highest quartile v. the lowest quartile were 0·72 (95 % CI 0·59, 0·87, P trend <0·001) for Fe from plants, 0·54 (95 % CI 0·45, 0·66, P trend <0·001) for Fe from white meat, 1·26 (95 % CI 1·04, 1·53, P trend =0·005) for haem Fe and 1·83 (95 % CI 1·49, 2·24, P trend <0·001) for Fe from red meat intake, respectively. However, no significant association was found between the consumption of total dietary Fe, non-haem Fe, Fe from meat and colorectal cancer risk. This study showed that lower intake of Fe from plants and white meat, as well as higher intake of haem Fe and Fe from red meat, were associated with colorectal cancer risk in a Chinese population.